Thiamin (vitamin B1, thiamine) transfer in the aquatic food web from lower to higher trophic levels. - Samuel Hylander; Hanna Farnelid; Emil Fridolfsson; Marc M Hauber; Vittoria Todisco; Maciej J Ejsmond; Elin Lindehoff (PLoS ONE)
Micronutrients such as vitamins are transferred from lower to higher trophic levels, but no general ecological concept describes the factors regulating this process. Here, we investigated thiamin (thiamine, vitamin B1), which is an example of a metabolically important water-soluble micronutrient. Thiamin is produced by organisms such as bacteria and phytoplankton, and all consumers, such as zooplankton and fish, rely on a continuous intake of thiamin through their diet and possibly from de novo-synthesized thiamin by gut microbiota. A deficiency in thiamin negatively affects reproduction in fish and bird populations worldwide. The aim of this study was to quantify thiamin transfer in a planktonic food web in response to thiamin and/or nutrient addition, using an outdoor mesocosm system (an approximately 1.9 m3 bag submerged in sea water). These estimates were then compared with literature data on thiamin concentrations at different trophic levels. The results showed that thiamin was rapidly taken up by phytoplankton in both the ambient and nutrient-amended treatments. However, large differences in thiamin concentrations in phytoplankton did not lead to any significant changes in community composition or abundance. Nitrogen addition led to changes in the abundance and community composition of picoplankton and phytoplankton but there were no additional major effects of thiamin addition. Differences in thiamin concentrations in phytoplankton were not detected at the next trophic level in zooplankton. Although the concentrations did not change, a greater abundance of some zooplankton taxa were developed in the thiamin treatments. Comparing the mesocosm results with literature data demonstrated a gradual reduction in thiamin concentrations along the food chain, with six percent of the concentration in producers occurring in top consumers (i.e., piscivorous fish). Overall, these observations illustrate the concept of trophic dilution of micronutrients where concentrations decrease along the food web from phytoplankton via zooplankton and planktivorous fish to piscivorous fish.